La collaboration dans le travail en groupe en contexte d’examen collaboratif à l’université - Diane Leduc; Mathilde Cambron-Goulet; André-Sébastien Aubin; Audrey Raynault (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The development of collaborative skills has become an important aspect of university education and a significant requirement for employability. It is not uncommon for teachers to use collaboration, through teamwork, to modulate their teaching and engage students. However, teamwork has its own set of difficulties, including the common problem of dividing up tasks without a clear overview and, consequently, without really collaborating. This observation leads us to this research question: how does collaboration manifest itself in group work at the university?To answer this question, we mobilized teamwork and collaboration literature that provide several conceptual frameworks. Landry's model (2010) appealed to us because it synthesizes all the processes at work in any small group. She postulates that there are three dynamic zones - work, affection and power - and that the evolution of the group is related to their interdependencies and their interactions. In our study, we placed students from a course in Philosophy of Education in teams of five to complete a summative collaborative exam in order to bring out the dimensions of collaboration and of the work zone. Our results indicate that the groups did not clarify the common goal, that the structuring of their work was adequate, that their decision-making was done in a collaborative way, and that they implicitly applied several norms concerning respect, attitudes and interactions. The study also highlights the importance of preparing and training both teachers and students to collaborate